2021
DOI: 10.1002/micr.30712
|View full text |Cite
|
Sign up to set email alerts
|

Total groin defect reconstruction by lymphatic flow‐through (LyFT) pedicled deep inferior epigastric artery perforator (DIEP) flap resorting to its superficial veins for lymphovenous anastomosis (LVA): A case report

Abstract: Extensive surgical removal is often required to treat soft tissue sarcomas. When they are localized in the groin‐upper medial thigh region, the excision is particularly demanding because of the rich lymphatic network and lymph nodes present in that area. The lymphatic vessels with respective lymph nodes draining the whole leg are most of the time inevitably damaged, causing a series of debilitating sequelae such as lymphocele and lymphedema. To prevent these issues, together with the defect coverage, additiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 20 publications
(19 reference statements)
0
9
0
Order By: Relevance
“…Scaglioni et al ( 119 ) reported a case of total groin defect reconstruction with a lymphatic flow-through, pedicled DIEP flap using its superficial veins for lymphovenous anastomosis with good outcomes. This article suggests that the lymphatic flow- through DIEP flap might be a new solution in cases requiring both dead space obliteration and lymphatic drainage restoration in regions such as the groin due to its proximity to the inguinal lymph nodes where seroma, lymphocele, and lymphedema are often unavoidable complications.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Scaglioni et al ( 119 ) reported a case of total groin defect reconstruction with a lymphatic flow-through, pedicled DIEP flap using its superficial veins for lymphovenous anastomosis with good outcomes. This article suggests that the lymphatic flow- through DIEP flap might be a new solution in cases requiring both dead space obliteration and lymphatic drainage restoration in regions such as the groin due to its proximity to the inguinal lymph nodes where seroma, lymphocele, and lymphedema are often unavoidable complications.…”
Section: Resultsmentioning
confidence: 99%
“…The authors found that in most cases, a pedicled flap was used, with the ALT flap being the most common. Our literature review found four other case reports or case series (47,48,117,119). All cases utilized the DIEP flap in pedicled fashion.…”
Section: Groin Reconstructionmentioning
confidence: 98%
See 1 more Smart Citation
“…A comprehensive search of several databases, from January 2000 to June 1, 2022, was conducted. We only found 5 publications reporting preventive surgery for lymphedema after sarcoma resection in the lower limb (Table 1) (Scaglioni et al, 2020; Scaglioni et al, 2021a; Scaglioni et al, 2021b; Scaglioni et al, 2022; Wagner et al, 2022). No randomized controlled clinical trials were available for review.…”
Section: Discussionmentioning
confidence: 99%
“…A significative comparison for this procedure is not feasible at this time since in the only published article by Di Summa (di Summa & Guillier, 2020) (with the name lymphatic flow‐through flap), a pedicled ALT flap was used. In our series of cases we managed to reconstruct a thigh defect resorting to a pedicled DIEP flap (Scaglioni et al, 2021c).…”
Section: Discussionmentioning
confidence: 99%